Conceptual metaphor as a method of forming stereotypical images in English media discourse - Yu. V. Akimtseva (Дискурс профессиональной коммуникации, 2020)
The conceptual metaphor has been one of the main topics for discussion in various scientific fields for many years. Its mental essence has become common knowledge, and therefore, the relationship between this phenomenon and both language and linguistic personality becomes obvious. It is this strong connection that determines the new vision of the conceptual metaphor from the position of its correlation with the picture of the world: from this perspective, the conceptual metaphor is viewed as a tool with which a picture of the world is formed and elaborated. The research shows that the conceptual metaphor is capable of creating an image that forms the basis of a picture of the world. In this case the image formed by the conceptual metaphor is stereotyped. The article examines stereotyped images represented by conceptual metaphors based on the English media discourse. It was revealed that the media discourse, which has ideological and influence functions, implements linguistic concepts through a conceptual metaphor. Subsequently, linguistic concepts are fixed and become stereotypes. Within the framework of the article, when considering the features of the linguistic and conceptual pictures of the world, the conclusion is drawn that the process of stereotyping is characteristic precisely for the conceptual picture of the world, which indicates the direct interconnection between the conceptual metaphor and the conceptual picture of the world.